Examining working and episodic memory in young adults with anhedonia. - Uribe, Sofia; Bowen, Holly J.; Meuret, Alicia E. (Cognitive, Affective & Behavioral Neuroscience, 2025)
Depression is associated with impairments in memory processes. Evidence suggests that poorer recognition of positive information and quicker disengagement with positive information from working memory in depressed versus nondepressed individuals. The working memory deficits are speculated to be downstream effects of a taxed working memory due to rumination processes that impair reward learning leading to anhedonia symptoms. Downstream effects are also hypothesized for episodic memory with impairments particularly for positive information due to dopamine dysregulation from anhedonia affecting memory formation processes. To examine the association of memory impairments in individuals with mild-to-severe anhedonia and depressive symptoms, 108 young adults completed a working memory task where they had to remember an abstract shape while presented with two consecutive positive, neutral, or negative images. This task was followed by a surprise episodic memory recognition test for the images the next day. The Drift Diffusion Model index drift rate was used to examine whether anhedonia severity predicted evidence accumulation rates during working and episodic memory retrieval. Contrary to expectations, based on multivariate models, anhedonia severity did not predict evidence accumulation rate for any specific valence in either task. These results suggest that anhedonia symptoms may not be uniquely associated with memory differences for emotionally valenced compared with neutral stimuli. Further studies should investigate the role of specific facets of anhedonia, including anticipatory reward and use different paradigms and neurophysiological measures, to examine the proposed hypotheses.